Factors that influence domestic tourists’ decision to visit nature-based tourism destinations in the northern region of Malaysia / Wan Sarah Shuhada Wan Shamshudi ... [et al.] - Wan Shamshudi, Wan Sarah Shuhada; Radzuan, Farah Nadiah; Faizal, Nur Faza Atiqa; Mohd Yazid, Siti Amalina; Md Yusof, Mohd Khairulanwar; Mohd Aznan, Ellail Ain (Universiti Teknologi MARA, Perlis, 2024)
Nature-based tourism is a growing trend that drives sustainable options within the tourism industry. This study aimed to explore the factors that influence domestic tourists’ decision to visit nature-based tourism in relation of six independent variables: nature, escape, activities, novelty, nostalgia, and attractions. A survey through a questionnaire was distributed to domestic tourists who travel to nature-based destinations. The research used descriptive analysis to investigate the demographic visitors that visit nature-based destinations. Regression analysis was used to identify the most popular reason for choosing the factors. The results of this study provide information to industry players and academics on domestic tourists’ preferences in nature-based tourism.